Positive effects of a cognitive-behavioral intervention program for family caregivers of demented elderly - Patrícia Paes Araujo Fialho; Anne Marise Köenig; Maria Dolores Lemos dos Santos; Maira Tonidandel Barbosa; Paulo Caramelli (Arquivos de Neuro-Psiquiatria)
OBJECTIVE: It was to examine the effects of a Cognitive-Behavioral Therapy (CBT) program administered to family caregivers of dementia patients. METHODS: Forty family caregivers were enrolled in a CBT intervention across eight weekly sessions. Cognitive, functional and behavioral status of patients were evaluated, as well as their own and their family caregivers' perceptions of quality of life. Specific instruments were also applied to evaluate caregiver stress level, coping, anxiety and depression. RESULTS: At the end of the program, family caregivers reported fewer neuropsychiatric symptoms among patients and an improvement in patients' quality of life. In addition, caregivers changed their coping strategies, whereas a significant decrease was observed in their anxiety levels. CONCLUSION: The CBT program employed appears to be a promising and useful tool for clinical practice, displaying positive effects on quality of life and neuropsychiatric symptoms of dementia, as well as proving beneficial for alleviating anxiety and stress in family caregivers.